“It’s not personal, it’s strictly business”: Historical Accounts and Archaeological Evidence Concerning an Early-Seventeenth Century Partnership - Fox, William (Ontario History, 2023)
Historical documentation is combined with archaeological evidence to examine the trade activity of two enterprising individuals, Iroquet and Brulé, who were peripheral to the grande histoire of New France during the early-seventeenth century. This article considers their modus operandi as it relates to established Indigenous intertribal exchange practices.